2020
DOI: 10.1111/1750-3841.15072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in‐package atmospheric cold plasma discharge on microbial safety and quality of ready‐to‐eat ham in modified atmospheric packaging during storage

Abstract: Listeria monocytogenes is often responsible for postprocessing contamination of ready-to-eat (RTE) products including cooked ham. As an emerging technology, atmospheric cold plasma (ACP) has the potential to inactivate L. monocytogenes in packaged RTE meats. The objectives of this study were to evaluate the effect of treatment time, modified atmosphere gas compositions (MAP), ham formulation, and post-treatment storage (1 and 7 days at 4°C) on the reduction of a five-strain cocktail of L. monocytogenes and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…can inhibit the spoilage bacteria growth such as Serratia spp. and Pseudomonas spp., due to their antibacterial activity and anti-oxidative activities (Yadav et al, 2020). Serratia spp.…”
Section: Comparative Effects On Bacterial Community Composition Of Chilled Beef During Storagementioning
confidence: 99%
“…can inhibit the spoilage bacteria growth such as Serratia spp. and Pseudomonas spp., due to their antibacterial activity and anti-oxidative activities (Yadav et al, 2020). Serratia spp.…”
Section: Comparative Effects On Bacterial Community Composition Of Chilled Beef During Storagementioning
confidence: 99%
“…However, unlike the beef loin, pork butt samples did not display significant increases in TBARS when compared to the control. In another study [50], ham was packed in three different gas mixtures, namely 20% O 2 , 40% N 2 and 40% CO 2 (treatment 1), 50% CO 2 and 50% N 2 (treatment 2) or 100% CO 2 (treatment 3) and treated at 30 kV for either 5 or 10 min using a dielectric barrier discharge (DBD) plasma system. The authors reported that TBARS values were significantly higher for the treated samples compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…These species react with different myoglobins in meats and meat products, thereby triggering oxidation of both pigment and lipids that alters the color of the DBD‐CAP‐treated samples. In contrast, the reason for no significant changes in color parameters might be because insufficient reactive species were produced that could not induce oxidation (Chaplot et al., 2019; Jayasena et al., 2015; Jung et al., 2017; Kim et al., 2013; Lee et al., 2016; Moutiq et al., 2019; Olatunde et al., 2019; Roh et al., 2019; Yadav et al., 2020; Yong et al., 2017; Zhuang, Rothrock et al., 2019a; Fröhling et al., 2012).…”
Section: Influence Of Cap On Processing and Sensory Parametersmentioning
confidence: 99%
“…For individual pathogens, for example, L. monocytogenes has a high hospitalization rate of > 90% and a fatality ranging from 20% to 30%. Equally, various kinds of meats are discarded annually in huge quantities due to these microorganisms, for example, over 16,000,000 kg of ground turkey was wasted as a result of Salmonella contamination (DeNoon, 2011; Hernandez‐Milian & Payeras‐Cifre, 2014; Roh et al., 2019; Russell, 2009; Tack et al., 2020; Thomas et al., 2015; Yadav et al., 2020; Zhuang, Rothrock et al., 2019a).…”
Section: Introductionmentioning
confidence: 99%